Glutamate as a non-conventional substrate for high production of the recombinant protein in Escherichia coli - Chiang, Chung-Jen; Hu, Mu-Chen; Ta, Thanh; Chao, Yun-Peng (Frontiers in Microbiology, 2022)
The economic viability of the biomass-based biorefinery is readily acknowledged by implementation of a cascade process that produces value-added products such as enzymes prior to biofuels. Proteins from the waste stream of biorefinery processes generally contain glutamate (Glu) in abundance. Accordingly, this study was initiated to explore the potential of Glu for production of recombinant proteins in Escherichia coli. The approach was first adopted by expression of D-hydantoinase (HDT) in commercially-available BL21(DE3) strain. Equipped with the mutant gltS (gltS*), the strain grown on Glu produced the maximum HDT as compared to the counterpart on glucose, glycerol, or acetate. The Glu-based production scheme was subsequently reprogrammed based on the L-arabinose-regulated T7 expression system. The strain with gltS* was further engineered by rewiring metabolic pathways. With low ammonium, the resulting strain produced 1.63-fold more HDT. The result indicates that Glu can serve as a carbon and nitrogen source. Overall, our proposed approach may open up a new avenue for the enzyme biorefinery platform based on Glu.